A general strategy for printing colloidal nanomaterials into one-dimensional micro/nanolines. Issue 47 (26th November 2018) - Li, Yifan; Zhang, Zeying; Su, Meng; Huang, Zhandong; Li, Zheng; Li, Fengyu; Pan, Qi; Ren, Wanjie; Hu, Xiaotian; Li, Lihong; Song, Yanlin
Abstract : A general strategy is demonstrated to print nanomaterials into 1D micro/nanolines with a multilayer or monolayer stack with a single-nanoparticle width. Abstract : Though patterned one-dimensional (1D) micro/nanoline arrays are of great importance in the field of integrated circuits and optoelectronics, the fabrication of high-precision micro/nanolines with excellent optical and electrical performance remains a great challenge. Herein, a general strategy for printing 1D micro/nanolines is proposed by manipulating the self-assembly of functional nanoparticles as a multilayer or monolayer stack with a single-nanoparticle width. This method is universal for dispersible nanoparticles, and the silver nanoparticle was selected as a model nanoparticle due to its good conductivity, dispersibility and narrow-size distribution. The results indicate that the morphologies of printed micro/nanolines can be precisely regulated by the substrate wettability and the suspension concentration. Specifically, 1D nanoparticle-assembled architectures are printed as a monolayer stack on the substrate with a low contact angle (below 45°), while a multilayer stack is formed on the substrate with a high contact angle (above 50°) or a high concentration (more than 0.12%). The controllability of micro/nanoline morphologies can be interpreted through the influence of the three phase contact line slipping motion and the nanoparticle diffusion on diverse substrates at different concentrations. Alteration of the printing template structures enables the intervals of 1D micro/nanolines to span from 16 μm to 48 μm. These results provide an efficient methodology for fabricating micro/nano-circuits or optics and strengthening the understanding of the self-assembling process.